The electromagnetic microwave sensors in improving speech intelligibility after laryngectomy - MIKOŁOWICZ, Mariusz (Archives of Acoustics, 2008)
The paper contains a short review of analytic, constructional and development investigations of low power electromagnetic microwave sensors (EMS) destined for applying them in laryngectophone system. General procedure rule and construction examples are presented. The measurement stand used to research signals produced by sensors of articulators' motion are described. Analytic method used to examine the usefulness of these signals to identify the vibrant phonemes is~reviewed.